What can we learn from Kurikulum Merdeka? A Systematic Literature Review of Kurikulum Merdeka's Influence on English Language Teaching Practices - Wahyudi, Asis; Visoni, Yon (Universitas Islam Negeri Raden Intan Lampung, 2025)
This literature review has highlighted both the potential and the challenges of implementing Kurikulum Merdeka in English language teaching in Indonesia. The curriculum aims to enhance students' communicative competence, autonomy, and engagement, and to align English language education with the demands of globalization. However, successful implementation requires addressing significant challenges, including teacher preparedness, resource constraints, and technical issues related to the use of supporting platforms. Overcoming these challenges will be crucial to realizing the full potential of Kurikulum Merdeka in transforming English language education and improving student outcomes.